Electric field effects on membranes: gramicidin A as a test ground. - Siu, Shirley Weng In; Böckmann, Rainer (Journal of Structural Biology, 2007)
Electric fields due to transmembrane potential differences or ionic gradients across the membrane are presumably crucial for many reactions across membranes or close to membranes like signal transduction, control of ion channels or the generation of neural impulses. Molecular dynamics simulations have been used to study the influence of external electric fields on a mixed gramicidin/phospholipid bilayer system. At high field strengths, formation of membrane electropores occurred both close and distal to the gramicidin. Gramicidin was found to stabilize the membrane adjacent to the protein but also at larger distances of up to 2-3 nm. As a result, membrane pore formation was found to be significantly suppressed for the mixed gramicidin/DMPC system. Moderate field strengths only weakly affected the structure and dynamics of the gramicidin. Spontaneous potassium passage events in external electric fields were observed for both the head-to-head helical conformation as well as for the double helical conformation of gramicidin A. The double-helical conformation was found to facilitate ion passage compared to the head-to-head helical dimer.